Women's History in the Pre-Independence Period and Its Involvement in Economic, Social, Politics, and Culture - Damayanty, Baiq Ira (CV. Sekawan Siji, 2024)
The Indonesian women's movement has a long history from pre-independence until today. Demands for equality in the eyes of the law and politics have been fought since pre-independence. The struggle carried out by Indonesian women aims to strive for equal rights that were fought for before independence until now. A review of women's movement studies not only provides an overview of women's struggles but also explains the representation of the women's movement in history. History shows that Indonesian women fought fervently for humanity and social justice. This study aims to provide an understanding of history as a foundation for the current women's movement in fighting for social and political rights. Therefore, Indonesian women leaders have set an example that today's women have the responsibility to continue this struggle.